The Contribution of Small and Medium Enterprise toward Economic Growth in South Sulawesi - Ramli, Anwar (Archives of Business Research, 2015)
Qualitative research with phenomenological approach as for the data source in this study include: 1) Primary Data Sources, 2) Secondary Data Sources. This research instrument is the researchers themselves, where the researcher as an instrument to obtain accurate data supplied by a variety of methods. The results showed that the experience of the current economic crisis hit Indonesia has proven that economic activity in the form of little people Small and Medium Enterprises constitute a major part in the economic activity of society that is able to withstand the storm of crisis as well as on South Sulawesi . Small and medium enterprises ( SMEs) has made a major contribution in the economy of Indonesia, both in terms of the amount of effort (establishment) and in terms of job creation